Forward guidance in an advanced small open economy in the effective lower bound - Marine Charlotte André; Guido Traficante (Banco de México, 2021)
We examine forward guidance (with known and uncertain duration) in a New Keynesian model for an advanced small open economy, showing that the response of the economy to this policy depends, both quantitatively and qualitatively, on some structural features through calibrations for Sweden and Spain. In particular, an announcement of future expansionary policy is positively related to the exchange rate pass-through and is larger than in the closed economy counterpart because of a better inflation-output trade-off and the exchange rate channel. We also show that multiple equilibria could arise and that the real exchange rate is a key variable driving this result. In particular, the response of output and inflation is amplified when aggregate supply is negatively related to the real exchange rate. These results could not necessarily be extended to emerging market economies.
Keywords: E31; E52; 330; Monetary policy; advanced small open economy; forward guidance